P PENGARUH KELUARAN SKOR KLINIS NIHSS TERHADAP KEJADIAN DELIRIUM PADA PASIEN STROKE - Diah Retno Wulan; Bella Aldila Erlida (LPPM Universitas Sari Mulia, 2020)
Background: The incidence of stroke is high every year and the problem can lead to more serious problems if not treated immediately. The severity of stroke patients needs to be measured to help doctors and nurses determine the right treatment and one of the assessment instruments that is considered valid to assess it is the National Institute of Health Stroke Scale (NIHSS). One of the neurological disorders that can be experienced by stroke patients related to stroke severity is delirium. Early detection of delirium is essential to enable immediate treatment that can help reduce the likelihood of poor prognosis. Objective: This study aims to determine the effect of NIHSS clinical score output on the incidence of delirium in stroke patients. Methods: The research design used in this study was cross sectional, the sample was stroke patients who were treated in the Stroke Center Room of RSUD Ulin Banjarmasin as many as 52 people, who were taken by probability sampling method. Data were analyzed using the Wilcoxon test. Results: The severity of stroke patients were mild (5.8%), moderate (38.5%), severe (23.1%), and very severe (32.7%). Patients who experienced delirium were 61.5% and did not experience as much as 38.5%. Based on statistical tests, the p value is 0.001, which describes the significant effect of NIHSS clinical value output on the incidence of delirium in stroke patients. Conclusion: There is a significant influence, namely the higher the output of NIHSS clinical scores, the greater the likelihood of delirium in stroke patients.